A study on hydropower water footprint affected by long-term evaporation in kenyir lake - Nornabila, Abu (2024)
Hydropower water footprint (HWFP) is a crucial metric in assessing water resource utilization by hydropower plants. It plays a pivotal role in evaluating historical water consumption and projecting future trends. Evaluating HWFP becomes more significant when greenhouse gases (GHGs) concentration rise rapidly, trapping more heat and eventually affecting the reservoir’s water availability for hydropower generation. Therefore, this study contributes to the comprehensive development of the long term HWFP affected by the long–term evaporation in Kenyir Lake, Terengganu. In projecting HWFP, the projection of the climate variables (rainfall, temperature, evaporation and relative humidity) and electricity supply (ES) were required since the equation governing the HWFP is linked to the evaporation rates from reservoirs and the electricity supply generated by hydropower plants. Climate data were collected from climate stations (1985-2022) provided by Department of Irrigation and Drainage (DID), Malaysian Meteorological Department (MMD), and Sultan Mahmud Power Station. Thus, the Statistical Downscaling Model (SDSM) version 4.1 was employed to analyze and project climate variables including future evaporation rates for the years 2025 - 2100. The Representative Concentration Pathways (RCP2.6, RCP4.5, and RCP8.5) from the IPCC Fifth Assessment Report (AR5) were used to generate plausible future weather scenarios for three different radiation levels. Subsequently, the relationships among these climate variables were investigated and the ES equation was developed using multiple linear regression. Finally, the HWFP was calculated based on the findings from ES projection, in combination with rainfall and evaporation rates. In this study, both the gross hydropower water footprint (GHWF) and net hydropower water footprint (NHWF) methods were used in obtaining the long-term pattern of HWFP. From the analysis, the rainfall trend is expected to decrease during the inter-monsoons and Southwest monsoon (dry season) but increase during the Northeast monsoon (wet season). The projection of maximum temperature under all the RCPs show a gradual increase, peaking from February to October with a range of 4.5 % to 6.5 % every 30 years. The projection of relative humidity is expected to decrease for all RCPs by about 4.5 % between 2070 to 2100 from November to January. The projected evaporation under all RCPs is expected to decrease by about 22 % and 24 %, with the biggest discrepancies occurring in September and November. From the backward elimination was found that the most significance variables are minimum temperature, mean temperature, and evaporation which had the smallest p-value and highest correlation coefficient, r. These variables were subsequently incorporated as independent variables within the ES equation. The results show that from 2025 to 2100, there will be significant increases in projected electricity supply in February, July and October. Meanwhile, the future HWFP is estimated to negatives, indicating a reverse situation where more water enters the reservoir instead of being evaporated. The GHWF in the past ranged from 2.5 m3 /GJ to 5 m3 /GJ from 1997 to 2020. In the future, the GHWF is expected to increase in particular months such as February, September, October and November. The results from this study is significant towards improvement of hydropower plant performance and development.